Manajemen Program Pendidikan Leadership untuk Siswa di Sekolah Alam Banyubelik Kedungbanteng Banyumas - Halimah Sadiyah; Mukh Adib Shofawi; Emiliya Fatmawati (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
This study aims to describe the management of leadership education programs for students in Banyumas Banyubelik Nature School Banyumas. This type of research used in this study is field research. Data collection techniques used were interviews, observation and documentation. Then the data analysis technique is done by data reduction, data presentation, and drawing conclusions. The results showed that the Management of Leadership Education Program for Students in the Banyu Belik Nature School had been implemented well. This can be proven by the achievement of the vision, mission and goals of the school which is to create a generation of ahlusunnah wal jama'ah who are ready to become leaders with moral mercy and scientific reasoning and have life skills in the field of leadership and technology by carrying out management functions including planning, organizing, implementing and controlling . Thus, the creation of educational institutions that can be moved as a whole as a whole in order to achieve the goals set.